The effect of phytochemicals in N-methyl-N-nitro-N-nitroguanidine promoting the occurrence and development of gastric cancer - Ling Lu; Bei Chen; XinYi Zhang; Yumeng Xu; Longtao Jin; Hui Qian; Zhao feng Liang (Frontiers in Pharmacology, 2023)
Gastric cancer is a common malignant tumor of the digestive tract, with a low early diagnosis rate. N-methyl-N-nitro-N-nitroguanidine (MNNG) is one of the main risk factors for gastric cancer. Phytochemicals are healthy active substances derived from vegetables, fruits, nuts, tea, herbal medicines and other plants. Taking phytochemicals is a very promising strategy for the prevention and treatment of gastric cancer. Many studies have proved that phytochemicals have protective effects on MNNG induced gastric cancer via inhibiting cell proliferation, enhancing immunity, suppressing cell invasion and migration, inducing apoptosis and autophagy, blocking angiogenesis, inhibiting Helicobacter pylori infection as well as regulating metabolism and microbiota. The intervention and therapeutic effects of phytochemicals in MNNG induced gastric cancer have attracted more and more attention. In order to better study and explore the role, advantages and challenges of phytochemicals in MNNG induced gastric cancer, we summarized the intervention and therapeutic effects of phytochemicals in MNNG induced gastric cancer. This review may help to further promote the research and clinical application of phytochemicals in MNNG induced gastric cancer, and provide some new insights.